Effects of preferred music on the anxiety of patients with acute respiratory failure undergoing weaning from the mechanical ventilator - Punzalan, Ma. Cecilia E.
This study investigated the effects of preferred music as an intervention on the anxiety level of patients with acute respiratory failure undergoing weaning from the mechanical ventilator. It also determined the difference of anxiety between the control and experimental group based on the socio-demographic variables. Despite numerous studies of music therapy on anxiety, no local study has been conducted to apply it to patients undergoing weaning from the mechanical ventilator, which is a lige threatening situation.The study utilized the post-test only control group design. A total of 30 patients participated in the study with 15 patients for the control and same number for the experimental group. The tools used to measure anxiety were the physiologic Response Rating Scale, Overt Anxiety Response Rating Scale and the Self-Report Anxiety Scale.To measure the effect of music on anxiety the t-test and ANOVA were used. Mean scores from the overt anxiety response rating scale and self report anxiety scale were compared for both the control and experimental group. Reduction in anxiety was based on the mean change of the physiologic parameters (systolic and diastolic blood pressure, heart rate and respiratory rate) from the baseline to the first, second, third and fourth hour of weaning.The results of the study did not support a significant change on the use of preferred music on the anxiety level of patients undergoing weaning from the mechanical ventilator. The study population consisted of 30 adult patients with ages varying from 25-60 years with the mean age of 44 years old. There was an almost equal distribution of male and female patients on both groups. Majority (66.6) of the patients was married. Almost 50of the patients reached highschool level. There are more non-breadwinners than the breadwinners. All patients had adequate support system. There was an almost equal distribution of charity and private patients on both groups. Reduction on anxiety was only significant in the systolic blood pressure change of about 8 mmHg from the baseline until the fourth hour of weaning as compared to an increase of 4 mmHg in the control group at .05 level. There is a trend towards lowering heart rate and respiratory rate among the music treated group. There was a significant difference in the head movement during weaning. In addition, no significant difference on anxiety was evident between the two groups based on the socio-demographic variables. However, patients perceived that music was helpful during the weaning process. It helped them relax and focus on the music.The results generated important implications to nursing practice, research and education. Music as an intervention should be provided and studied on different clientele groups. This may serve to enhance their well being and improve quality of life. This study would also serve as a basis for planning and implementing training programs that will contribute to better quality care to our patients. For the program to be effective, music hsa to be easily accessible to patients. Cassette players with earphones and tapes will be supplied to the unit. This can be stored in mobile carts. A staff nurse should be responsible for the equipment. The nurses should be trained how to initiate the music considering all the variables. And they should be well versed on the protocol of the program.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Music therapy; Anxiety